A computer-aided learning package for Chinese calligraphy / Low Peng Fong - Low , Peng Fong (2003)
One of the most rapidly changing and exciting areas of learning in the world today is the development of computer-based learning materials, especially interactive learning programs that run on personal computers. These programs offer users a brand new experience in the learning world. Through the condensed storage capabilities of computers, multimedia can deliver large amounts of information in ways that make it manageable, approachable and useful. By making it possible to access illustrations and photographs, sound and video, as well as large amounts of text, interactive multimedia programs present learning information to users in a newly engaging and meaningful way. This report presents the development of a courseware, which aims to build a computer-aided learning package for Chinese calligraphy. (CHICALEP). This learning package is developed for any users from all ages who wish to learn Chinese calligraphy. The prototyping approach was selected for the development process because it supports Rapid Application Development (RAD) and reduces the risks involved. Software engineering principles based on this approach were applied throughout the development phases of system analysis, system design, implementation, evaluation and testing. Main functions included in this package are introduction and historical evaluation of Chinese Character, structures of Chinese character, four precious tools of Chinese calligraphy, different levels of exercise and assessment, assessment results, maintenance and help. This package was developed using combination of graphic tool, multimedia tool. Language tool and programming tools which included Adobe Photoshop 7.0, Macromedia Flash MX Version 6.0, Chinese Star XP. And Microsoft Visual Basic 6.0.